The Effect of Utilizing Business Model Canvas on the Satisfaction of Operating Electronic Business. (1st September 2022) - Fakieh, Bahjat; AL-Malaise AL-Ghamdi, Abdullah S.; Ragab, Mahmoud
Abstract : The Business Model Canvas (BMC) is a strategic model for developing business organizations' roadmap toward achieving their goals. While several organizations utilize the Business Model Canvas (BMC) to establish and operate their businesses well, the utilization of BMC seems to be limited in the local market of Saudi Arabia, especially when businesses utilize electronic business channels. This paper aims to explore the status of the utilization of BMC among Saudi SMEs, as a critical sector. The paper highlights the awareness and practice of BMC's nine factors before and during the operation of e-commerce stores by Saudi SMEs. Then, it aims to explore the significance of practicing those factors in increasing the satisfaction level of running businesses. In this paper, a quantitative survey was distributed conveniently to 200 SMEs in the two largest Saudi cities, which are Riyadh (the capital) and Jeddah (the country's main seaport), resulting in 63 valid participations from different industries. After operating e-commerce stores, most SMEs gained more knowledge of five BMC factors: key partners, value propositions, customer relationships, customer segments, and cost structures. Meanwhile, they found some issues in the other four factors: key activities, key resources, channels, and revenue streams. The proposed method exposes the variety of results and indicates a lack of understanding of BMC by the examined e-commerce SME samples, as they depend on traditional methods of identifying the elements of each of the BMC factors.